Sjögren's syndrome associated with celiac disease - Silva, Felipe Freire; Lerner, Aaron; Geber Júnior, João Carlos; de Carvalho, Jozélio Freire; Shoenfeld, Yehuda (International journal of celiac disease, 2020)
Background: Autoimmune diseases tend to run in families and the affected persons are prone to additional autoimmune conditions. This is the case for celiac disease (CD) and Sjögren's syndrome (SS). Objectives: To describe a patient with both diseases and to analyze the clinical, therapeutic and evolutionary characteristics of published patients with SS associated with CD. Methodology: A systematic review of articles published in PubMed, MEDLINE, LILACS and Scielo dating from 1966 to May 2020, was conducted, using the following search words: Sjögren's syndrome, Celiac disease. Only English, German and French publications were considered. Results: Only 16 studies with 31 patients with SS associated CD were depicted. Adding the present case would mount the total to 17 studies, describing 32 patients. There are 6 observational studies and 10 case reports. In relation to demographics, age varied from 10 to 73 years old, with a median of 45 years and the great majority were female (21/32 patients). SS preceded CD manifestations in 7 studies, CD was the first presentation in 6 articles and simultaneous diseases was observed in 4 reports. Time elapsed between the two diseases varied from 2 to 33 years. Autoantibodies related to SS showed that anti-Ro and anti-La were positive in 8/17, while CD-related antibodies were positive in 12/17 studies. Regarding therapy, the majority received a gluten-free diet as CD therapy (13/17 studies). Glucocorticoid was prescribed in 6/17 studies and hydroxychloroquine in 4/17. When described, all studies demonstrated improvement of CD manifestations and 7/17 improved SS symptoms. Conclusion: The present comprehensive review evaluated all published cases of SS and CD of the literature. In the majority, SS precedes CD and all patients had good responses to appropriate therapy. It is hoped that increased awareness of the combination of SS and CD will result in earlier diagnosis and therapy and improved outcome.
Keywords: dospělí; prednison; Female; azathioprin; Hydroxychloroquine; Diet, Gluten-Free; intersticiální plicní nemoci; Adult; výsledek terapie; ženské pohlaví; Autoimmune Diseases; lidé; vitamin D; Treatment Outcome; Dermatitis Herpetiformis; klinická studie jako téma; Prednisone; Clinical Studies as Topic; Vitamin D; Sjögrenův syndrom; autoimunitní nemoci; Humans; Azathioprine; hydroxychlorochin; Male; Aged; Lung Diseases, Interstitial; Autoantibodies; dermatitis herpetiformis; bezlepková dieta; Celiac Disease; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Sjogren's Syndrome; celiakie; autoprotilátky